قاعدة العمل بالأولى في الفقه المالكي - تأصيلا وتفريعا - موفق, نبيل (جامعة الوادي University of Eloued, 2016)
يناقش هذا المقال موضوع فقه الأولويّات بين التّأصيل والتّعليل، ويبين أنّ العمل بالأولى والأحرى من القواعد الكبرى في الاجتهاد المقاصدي النّظري والتّطبيقي، له أصوله وأدلّته من القرآن والسنّة النّبويّة -سواءً أكان ذلك في السنّة القولية أم الفعلية- ومن أقوال الصّحابة-رضي الله عنهم- وأقضيتهم واجتهاداتهم، كما يبين أنّ قاعدة فقه الأولويات قاعدة معتبرة عند الفقهاء وعلى رأسهم أئمّة المذاهب الأربعة، وأنّ المذهب المالكي من خلال قواعده وفروعه الفقهيّة قد أسهم إسهاماً فعّالاً في تقعيد ذلك الفقه. Abstract: This article discusses the subject of the jurisprudence of priorities between the rooting and reasoning shows that work more: Rather than major bases in the diligence Makassed theoretical and applied , his assets and evidence from the Qur'an and Sunnah -whether it be in anecdotal year or Alflah- and the sayings of the Companions - may Allah be pleased Anhm- and Oqdathm and reasoning , also shows that the jurisprudence Base Base priorities when considering jurists , led by the imams of the four schools , and that the Maliki school of its branches through its rules and jurisprudence has contributed to an effective contribution to the social market that jurisprudence.
Jurisprudence Of Priorities Rule In Fiqh Al-maliki Between The Rooting And Reasoning
Keywords: القواعد، الأصول، التطبيق، الأولوية، الفقه، المالكية; rules - oussoul - Application - priority - Fiqh - Maalikis